2022
DOI: 10.3390/molecules27175435
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics-Guided Identification of Ethyl Acetate Extract of Citri Reticulatae Pericarpium as a Functional Food Ingredient with Anti-Inflammatory Potential

Abstract: Citri Reticulatae Pericarpium (CRP) is one of the most commonly used food supplements and folk medicines worldwide, and possesses cardiovascular, digestive, and respiratory protective effects partially through its antioxidant and anti-inflammatory functions. The unique aromatic flavor and mild side effects make CRP a promising candidate for the development of anti-inflammatory functional food. However, recent studies show that the crude alcoholic extract and some isolated compounds of CRP show compromised anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…To date, the effect of SNS on mediating immunocytes activities remains largely elusive. It is reported that flavonoids, but not SNS, significantly decreased LPS-induced inflammatory cytokines in macrophages via bioinformatics and in vitro approach, such as TNF-α and IL-6 production . However, others reported that SNS performed as an immunity enhancer counters immunosuppression via elevating transcription and secretion of IFN-γ, IL-2, and IL-6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the effect of SNS on mediating immunocytes activities remains largely elusive. It is reported that flavonoids, but not SNS, significantly decreased LPS-induced inflammatory cytokines in macrophages via bioinformatics and in vitro approach, such as TNF-α and IL-6 production . However, others reported that SNS performed as an immunity enhancer counters immunosuppression via elevating transcription and secretion of IFN-γ, IL-2, and IL-6 .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that flavonoids, but not SNS, significantly decreased LPS-induced inflammatory cytokines in macro- phages via bioinformatics and in vitro approach, such as TNF-α and IL-6 production. 29 However, others reported that SNS performed as an immunity enhancer counters immunosuppression via elevating transcription and secretion of IFN-γ, IL-2, and IL-6. 30 To further confirm the role of SNS in regulating macrophagic activities in inflammatory injury, we performed in vitro and in vivo studies and then found that macrophage indeed largely infiltrated in LPS-induced injury sites, which accompanied with releasing massive pro-inflammatory cytokines, including TNF-α, IL-1β, and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…And except for its medicinal value with abundant resources, Citrus reticulata Blanco is also an edible material with highly exploitable value. Modern studies correlated to its pharmacological actions, biological activities, and clinical applications have revealed that treatment of cardiovascular disease 1 , anti-oxidant 2 , anti-inflammatory 3 , anti-tumor 4 as well as reducing blood lipid are its important effects 5 . However, with the development of evidence-based medicine and/or evidence-based pharmacy, clarification of the active secondary metabolites in Citri Reticulatae Pericarpium is the fundamental science, which needs to be systematically addressed.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the most serious obstacle in the natural products development and research is to establish the best quality control method by identifying the representative active chemical constituents in the preparations, especially for complex herbal preparations [ 10 ]. The main active components of these eight herbs in Fuzhengjiedu Granules are as follows: chlorogenic acid (S 1 ), neochlorogenic acid (S 2 ), cryptochlorogenic acid (S 3 ), caffeic acid (S 5 ), isochlorogenic acid C (S 10 ), and isochlorogenic acid A (S 12 ) in JYH, protocatechuic aldehyde (S 4 ) and syringic acid (S 6 ) in ZJC, liquiritin (S 7 ), isoliquiritin (S 8 ), neoisoliquiritin (S 14 ), neoliquiritin (S 16 ), liquiritigenin (S 18 ), isoliquiritigenin (S 24 ), and licochalcone A (S 28 ) in GC, naringin (S 9 ), hesperidin (S 11 ), naringenin (S 22 ), and hesperetin (S 25 ) in CP, benzoylmesaconine (S 13 ), benzoylaconine (S 15 ), benzoylhypaconine (S 17 ), mesaconitine (S 19 ), aconitine (S 20 ), and hypaconitine (S 21 ) in DFP, psoralen (S 23 ) and bergapten (S 26 ) in WZMT, 6-gingerol (S 27 ) in GJ, and pogostone (S 29 ) in GHX [ 7 , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] ], respectively. Related literature and studies have shown that these twenty-nine compounds are the foremost active ingredients in each individual.…”
Section: Introductionmentioning
confidence: 99%